Penerapan Balanced Scorecard Sebagai Alat Ukur Kinerja Organisasi pada PT Yanaha - Maria Anjelina Mono; Agustina Berti; Fransiskus Leta; Apolionarois Loda Teluma; Maria Silvana Mariabel Carcia (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to analyze the implementation of the Balanced Scorecard (BSC) as a tool for measuring organizational performance at PT YANAHA. The Balanced Scorecard is a performance measurement method that integrates financial and non-financial aspects through four perspectives: financial, customer, internal business processes, and learning and growth. This research uses a descriptive qualitative approach through interviews, observations, and documentation studies. The results show that the implementation of BSC provides a comprehensive overview of company performance and assists in strategic decision-making.